Multiple targets identified with genome wide profiling of small RNA and mRNA expression are linked to fracture healing in mice - Bourgery Matthieu; Ekholm Erika; Fagerlund Katja; Hiltunen Ari; Puolakkainen Tero; Pursiheimo Juha-Pekka; Heino Terhi; Määttä Jorma; Heinonen Jussi; Yatkin Emrah; Laitala Tiina; Säämänen Anna-Marja (Elsevier BV, 2022)
Long-bone fracture is a common injury and its healing process at the fracture site involves several overlapping phases, including inflammation, migration of mesenchymal progenitors into the fracture site, endochondral ossification, angiogenesis and finally bone remodelling. Increasing evidence shows that small noncoding RNAs are important regulators of chondrogenesis, osteogenesis and fracture healing. MicroRNAs are small single-stranded, non-coding RNA-molecules intervening in most physiological and biological processes, including fracture healing. Angiogenin-cleaved 5' tRNA halves, also called as tiRNAs (stress-induced RNAs) have been shown to repress protein translation. In order to gain further understanding on the role of small noncoding RNAs in fracture healing, genome wide expression profiles of tiRNAs, miRNAs and mRNAs were followed up to 14 days after fracture in callus tissue of an in vivo mouse model with closed tibial fracture and, compared to intact bone and articular cartilage at 2 months of age. Total tiRNA expression level in cartilage was only approximately one third of that observed in control D0 bone. In callus tissue, 11 mature 5'end tiRNAs out of 191 tiRNAs were highly expressed, and seven of them were differentially expressed during fracture healing. When comparing the control tissues, 25 miRNAs characteristic to bone and 29 miRNAs characteristic to cartilage tissue homeostasis were identified. Further, a total of 54 out of 806 miRNAs and 5420 out of 18,700 mRNAs were differentially expressed (DE) in callus tissue during fracture healing and, in comparison to control bone. They were associated to gene ontology processes related to mesenchymal tissue development and differentiation. A total of 581 miRNA-mRNA interactions were identified for these 54 DE miRNAs by literature searches in PubMed, thereby linking by Spearman correlation analysis 14 downregulated and 28 upregulated miRNAs to 164 negatively correlating and 168 positively correlating miRNA-mRNA pairs with chondrogenic and osteogenic phases of fracture healing. These data indicated that tiRNAs and miRNAs were differentially expressed in fracture callus tissue, suggesting them important physiological functions during fracture healing. Hence, the data provided by this study may contribute to future clinical applications, such as potential use as biomarkers or as tools in the development of novel therapeutic approaches for fracture healing.